STANDARDIZATION OF MODEL OF INDUCTION OF HEPATOTOXICITY WITH ANTI-TUBERCULOSIS DRUGS IN WISTAR ALBINO RATS - Kapgate, Sarita M; Patil, Abhijit B (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The objective of the study to standardize the model of hepatotoxicity induced by ATT drugs in Wistar Albino rats. Isoniazid (INH), rifampicin (RMP), pyrazinamide (PZA), the first line drugs used in the treatment of tuberculosis (TB) associated with the potential adverse effect. Numerous animal studies were reported endeavoring induction and cure of anti-TB (ATT) drug-induced hepatotoxicity using herbal and chemical drugs. However, the previous reported study failed to replicate where Wistar albino rats were treated with INH, RMP, and PZA and had shown the significant development of liver injury. Hence in present paper, aimed to develop a standardize model of induction of hepatotoxicity with ATT drugs. Methods: Wistar rats were treated with ATT drugs in combination in various doses up to 4-8 weeks. Total nine experiments were conducted to achieve successful hepatotoxicity. The aspartate aminotransferase (AST), alanine aminotransferase (ALT), and alkaline phosphatase (ALP) were the biochemical parameters of assessment. Histopathological changes in the liver were also examined. Results: No evidence of any liver injury or an inflammatory infiltrate has been observed as had been reported in the previous studies. Rather decrease in serum ALT levels has been observed by researcher. In short, hepatic injury cannot be developed with the doses used in previous reported papers. The successful attempt to induce hepatotoxicity can be achieved with the doses of INH - 100, RMP - 300, PZA - 700 mg/kg. The findings were confirmed by the raised ALT, AST, and ALP levels compared with baseline. The histopathological changes also support the findings. Conclusion: The dose of INH - 100, RMP – 300 and PZM - 700 mg/kg. Succeeds to induce hepatotoxicity in Wistar albino rats and Swiss albino mice as well.